PENGARUH STRUKTUR MODAL, KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Risa, Sofia; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to examine the partial and simultaneous effects of capital structure, managerial ownership and firm size on corporate value. Where independent variable in this research is capital structure, managerial ownership and company size while dependent variable is company value. Using secondary data in form of financial statements, base and chemical industry sector listed on Indonesia stock exchange in 2011-2015. Sampling method used purposive sampling. The sample used is 7 companies base and chemical industry sector listed on Indonesia stock exchange . Data analysis techniques used are simple linear regression and multiple linear regression. The result of research partially ( t test) show that capital structure (DAR, DER, LtDER) have positive significant effect to firm value (PBV), managerial ownership (KM) has negative effect to firm value, and firm size (Ln asset) have positive and significant influence to firm value. While simultaneously (f test) capital structure, managerial ownership and firm size have positive and significant influence to company value.KeyWords : capital structure, managerial ownership, firm size, firm value